The Case of Time Axis Fallacy: 11th Grade Students' Intuitively-based Misconception in Probability and Teachers' Corresponding Practices - Mehmet Fatih Öçal (Anı Publishing, 2018)
This case study aimed to investigate whether mathematics teachers' instructional practices were effective in resolving eleventh grade students' intuitively-based misconceptions regarding time axis fallacy. The participants were three mathematics teachers from different high schools and their students. Students were administered a diagnostic test comprising questions related to intuitively-based misconceptions in probability. The test was administered before and after students received teachers' instructions for probability subject. Teachers were interviewed about their knowledge of students' difficulties and misconceptions. Teachers' instructions for probability were observed and videotaped. Content analysis method was used in the data analysis. Considering the findings, it was observed that teachers did not give emphasis on unfamiliar situations related to time axis fallacy. Comparing the test results, there was slight increase in the number of students who fell into time axis fallacy. Based on the findings, it can be asserted that practitioners should be aware of possible intuitively-based misconceptions in probability and organize their instructions accordingly.